2021
DOI: 10.3390/cancers13163958
|View full text |Cite
|
Sign up to set email alerts
|

Early Tumor Response and Safety of Atezolizumab Plus Bevacizumab for Patients with Unresectable Hepatocellular Carcinoma in Real-World Practice

Abstract: The aim of this study was to investigate the early tumor response and safety of atezolizumab plus bevacizumab for patients with unresectable hepatocellular carcinoma in real-world practice. Forty patients with Child-Pugh class A liver function and eastern cooperative oncology group performance status 0 or 1 were enrolled. The objective response rate (ORR) at six weeks after the start of treatment, changes in α-fetoprotein (AFP) and des-γ-carboxyprothrombin, incidence of adverse events (AEs), and changes in alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
1
34
3
Order By: Relevance
“…In the IMbrave150 trial, patients receiving atezolizumab plus bevacizumab had an ORR of 33.2% and a DCR of 72.3% according to mRECIST and the median PFS was 6.9 months 1,13 Similarly, in the present study, the Atezo + Beva group had an ORR of 43.8% and a DCR of 76.6% according to mRECIST, and the median PFS was 8.8 months. Some previous clinical studies have reported the early experience of atezolizumab plus bevacizumab therapy as primary systemic chemotherapy for HCC, with the ORRs reportedly ranging from 31.8% to 37.5% and the DCRs reportedly ranging from 81.3% to 94.5% according to mRECIST 14–17 . The DCRs in these clinical practice studies, and the ORR and the PFS in our study were slightly better than those from the IMbrave150 trial.…”
Section: Discussioncontrasting
confidence: 42%
“…In the IMbrave150 trial, patients receiving atezolizumab plus bevacizumab had an ORR of 33.2% and a DCR of 72.3% according to mRECIST and the median PFS was 6.9 months 1,13 Similarly, in the present study, the Atezo + Beva group had an ORR of 43.8% and a DCR of 76.6% according to mRECIST, and the median PFS was 8.8 months. Some previous clinical studies have reported the early experience of atezolizumab plus bevacizumab therapy as primary systemic chemotherapy for HCC, with the ORRs reportedly ranging from 31.8% to 37.5% and the DCRs reportedly ranging from 81.3% to 94.5% according to mRECIST 14–17 . The DCRs in these clinical practice studies, and the ORR and the PFS in our study were slightly better than those from the IMbrave150 trial.…”
Section: Discussioncontrasting
confidence: 42%
“…Another group from Japan published real-world data concerning tumor response and safety for atezolizumab/bevacizumab in 40 patients with Child–Pugh A cirrhosis [ 17 ]. Twenty-four patients had a previous treatment experience with molecular agents (TKI).…”
Section: Discussionmentioning
confidence: 99%
“…Several real-world clinical studies have shown that Atezo/Bev therapy has comparable safety profiles and efficacy, as observed in the IMbrave150 study [4,5]. However, the objective response rate (ORR) and disease control rate (DCR) reported for Atezo/Bev in the updated analysis of the IMbrave150 trial are 29.8% and 73.9%, respectively [6].…”
Section: Introductionmentioning
confidence: 94%